Impact of quadrivalent influenza vaccine on public health and influenza-related costs in Australia. (December 2016) - Jamotte, Aurélien; Chong, Chui; Manton, Andrew; Macabeo, Bérengère; Toumi, Mondher
Abstract Background Annual trivalent influenza vaccines (TIV) containing three influenza strains (A/H1N1, A/H3N2, and one B) have been recommended for the prevention of influenza. However, worldwide co-circulation of two distinct B lineages (Victoria and Yamagata) and difficulties in predicting which lineage will predominate each season have led to the development of quadrivalent influenza vaccines (QIV), which include both B lineages. Our analysis evaluates the public health benefit and associated influenza-related costs avoided which would have been obtained by using QIV rather than TIV in Australia over the period 2002–2012. Methods A static model stratified by age group was used, focusing on people at increased risk of influenza as defined by the Australian vaccination recommendations. B-lineage cross-protection was accounted for. We calculated the potential impact of QIV compared with TIV over the seasons 2002–2012 (2009 pandemic year excluded) using Australian data on influenza circulation, vaccine coverage, hospitalisation and mortality rates as well as unit costs, and international data on vaccine effectiveness, influenza attack rate, GP consultation rate and working days lost. Third-party payer and societal influenza-related costs were estimated in 2014 Australian dollars. Sensitivity analyses were conducted. Results Using QIV instead of TIV over the period 2002–2012 would have prevented an estimated 68, 271 additional influenza cases, 47, 537 GP consultations, 3, 522 hospitalisations and 683 deaths in the population at risk of influenza. These results translate into influenza-related societal costs avoided of $46.5 million. The estimated impact of QIV was higher for young children and the elderly. The overall impact of QIV depended mainly on vaccine effectiveness and the influenza attack rate attributable to the mismatched B lineage. Conclusion The broader protection offered by QIV would have reduced the number of influenza infections and its related complications, leading to substantial influenza-related costs avoided.